Effects of surgical mandibular advancement on the upper airways of adult class II patients: A systematic review with meta‐analysis. (13th January 2021) - Bucci, Rosaria; Rongo, Roberto; Bucci, Paolo; Valletta, Rosa; Michelotti, Ambrosina; D'Antò, Vincenzo
Abstract: Aim: To systematically review the effects of surgical mandibular advancement (SMA) regarding changes of the upper airways in adult patients with skeletal Class II malocclusion. Materials and Methods: Five electronic databases were searched up to April 2020. Human studies focusing on the morphology and dimension of the upper airways after SMA were included. 'Quality assessment for Before‐After (Pre‐Post) Studies' was used to assess the risk of bias of the individual studies. Standard mean differences (SMD) with 95% confidence intervals (CI) were calculated for random effect model meta‐analysis. The certainty of evidence was assessed using the GRADE tool. Results: Twenty cohort studies of only treated patients without control group were eligible for qualitative synthesis, of which 17 were used for quantitative synthesis. Very low certainty of evidence indicated that SMA resulted in significant increase of the volume and of the smallest cross‐sectional area (SMC) of the nasopharynx (volume SMD: 1.43, CI: 0.62, 2.24, P = .001, I 2 = 87.8%; SMC SMD: 1.53, CI: 0.59, 2.47, P = .001, I 2 = 90.5%) and oropharynx (volume SMD: 1.36, CI: 0.37, 2.35, P = .007, I 2 = 92.1%; SMC SMD: 1.21, CI: 0.11, 2.32, P = .032, I 2 = 93.1%). Significant augmentation of the distances between the posterior pharynx wall and the uvala (SMD: 0.73, CI: 0.46, 0.98, P < .001, I 2 = 72.7%), the posterior border of the tongue (SMD: 0.52, CI: 0.21, 0.84, P = .001; I 2 : 60.5%), the gonion (SMD: 1.24, CI: 0.56, 1.91, P < .001; I 2 = 88.8%) and the epiglottis (SMD: 0.40, CI: 0.06, 0.74, P = .033; I 2 = 84.8%) were observed. Conclusions: Weak evidence suggests enlargement of the upper airways of adult Class II subjects following SMA, with major increases in the oropharynx.